A hospital-wide initiative to redesign substance use disorder care: Impact on pharmacotherapy initiation. Issue 4 (October 2021) - Wakeman, Sarah E.; Kane, Martha; Powell, Elizabeth; Howard, Sydney; Shaw, Christopher; Kehoe, Laura; Rosen, Joy; Quinlan, Joan; Regan, Susan
Background: Substance use disorder (SUD) treatment in general medical settings remains underutilized. We evaluated 5 years of a hospital-wide SUD initiative which included an inpatient addiction consult team (ACT), low-threshold Bridge Clinic, recovery coaches, and office-based addiction treatment (OBAT) nurses. Methods: Naturalistic registry study. We calculated frequencies of patient contacts, types of substance use diagnoses, and medication treatment initiation and duration. Results: From 2014 to 2019, 7, 036 unique patients were seen, including 4, 959 by ACT, 1, 197 in Bridge Clinic, 2, 250 by a recovery coach, and 979 by an OBAT nurse. The median age was 47, 31% were women, 80% were white, 7% were black, 6% were Hispanic/Latinx, and 25% were experiencing homelessness. Alcohol use disorder was seen in 62%, opioid use disorder in 54%, cocaine use disorder in 29%, benzodiazepine use disorder in 14%, and stimulant use disorder in 7%. Co-occurring medical and psychiatric illnesses were common; 35% had hepatitis C, 59% depression, 66% anxiety, and 13% schizophrenia. 1, 623 patients received a prescription for buprenorphine during the study period (42% of patients with OUD), 877 for oral naltrexone, and 163 for extended-release naltrexone. The mean length of continuous treatment was 178.4 days for buprenorphine, 47.7 days for oral naltrexone, and 1.29 injections for extended-release naltrexone. Conclusion: A hospital SUD initiative effectively initiated SUD pharmacotherapy with naltrexone and buprenorphine. Medication treatment episodes were longer with buprenorphine.